2004
DOI: 10.1089/104454904773819798
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr: Genetic Diversity and Functional Features from the Perspective of Structure

Abstract: RNA viruses are well known for the enormous genetic variation. Retroviruses share this feature with other RNA viruses, and human immunodeficiency virus type 1 (HIV-1) has been extensively investigated in this regard. Based on the DNA sequence analysis, HIV-1 has been classified into three groups; M, N, and O, with viral subtypes in each group. While the genetic variation between viral isolates has been documented throughout the genome, specifically, the env gene exhibits high variation. Analysis of the env gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 146 publications
0
11
0
Order By: Relevance
“…23,24 The 14 kDa HIV-1 late accessory protein, Vpr, has received significant attention due to its regulatory effect upon virus and host functions. [25][26][27] At the cellular level, expression of Vpr results in deregulation of the cell cycle and accumulation of the cells at the G 2 /M stage of the cell cycle, [28][29][30] which may result in cell death. In addition, expression of Vpr can induce apoptosis through a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The 14 kDa HIV-1 late accessory protein, Vpr, has received significant attention due to its regulatory effect upon virus and host functions. [25][26][27] At the cellular level, expression of Vpr results in deregulation of the cell cycle and accumulation of the cells at the G 2 /M stage of the cell cycle, [28][29][30] which may result in cell death. In addition, expression of Vpr can induce apoptosis through a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is plausible that in HIV-1 subtype C infection, two conserved arginine residues at positions 73 and 80 are sufficient for adenine nucleoside translocator interaction. 36 Other well-known substitutions, such as E21P, E24P, and A59P, which prevent the incorporation of Vpr into virus-like particles, as well as Q65R, which is correlated with impairment of Vpr docking at the nuclear envelope, 59 were not observed in this study. Neither were other known substitutions, underlying the integrity of Vpr during early HIV-1C infection.…”
mentioning
confidence: 56%
“…Several other studies showed marked heterogeneity in vpr sequences derived from multiple patient samples Kuiken et al, 1996). In addition to length polymorphisms, numerous studies have demonstrated an association between substitution mutants in the amino acid sequence of Vpr and disease (Caly et al, 2008;Lum et al, 2003;Tungaturthi et al, 2004). Caly et al (2008) found a mutation, F72L, in several vpr sequences derived from a single patient with LTNP status.…”
Section: Vpr Polymorphisms Across Subtypesmentioning
confidence: 97%
“…After seroconversion to HIV-positive status, the viral loads measure at 10000-50000 viral RNA copies per ml of patient sera during the asymptomatic A Mutagenesis Approach for the Study of the Structure-Function Relationship of Human Immunodeficiency Virus Type 1 (HIV-1) Vpr 205 stage; in the later stages of disease, viral RNA genomes can increase to several million copies per ml (Poropatich and Sullivan, 2011;Tungaturthi et al, 2004). Thus, a high replication rate produces tremendous variation in the viral population within a single patient.…”
Section: Heterogeneity In the Human Immunodeficiency Virusmentioning
confidence: 99%
See 1 more Smart Citation